Orderly integrated fuel cell membrane electrode and its preparation method and application

By designing polygonal micro-cell array structure and adjacent angle gap junction catalysts in fuel cell membrane electrodes, the problem of flooding of large-area membrane electrodes is solved, oxygen transmission efficiency and catalyst activity are improved, and high power density and low cost fuels are achieved Battery performance is improved.

CN118738480BActive Publication Date: 2024-12-20BEIJING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411204877.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-20
Estimated Expiration
2044-08-29

AI Technical Summary

Technical Problem

Large-area membrane electrodes in fuel cells are prone to flooding during use, resulting in increased oxygen transmission resistance and catalysts cannot effectively contact the reaction gas, resulting in a decline in battery performance. The existing solutions are costly and complex in production, which is not conducive to large-scale Large-scale production.

Method used

Using an ordered integrated fuel cell membrane electrode, the polygonal micro-cell array structure is designed in the cathode catalytic layer, and adjacent side gaps are set to ensure liquid or gas flow, reduce oxygen transmission resistance, and pass adjacent side Angular gap connects the catalyst to promote the discharge of water and gas and improve the uniform distribution of current.

Benefits of technology

It effectively alleviates the flooding problem, improves the power density and catalyst activity of the membrane electrode, reduces production costs, is suitable for large-scale production applications, and improves the overall performance of fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118738480B_ABST
    Figure CN118738480B_ABST
Patent Text Reader

Abstract

The present invention discloses an ordered integrated fuel cell membrane electrode and a preparation method thereof, which belongs to the field of fuel cells. It comprises: a cathode catalyst layer, the cathode catalyst layer comprises a plurality of tiny units, the tiny units are distributed in an array, and the tiny units comprise cathode catalysts; wherein the shape of the tiny units is a polygon; a straight adjacent edge gap is arranged between adjacent edges of each of the tiny units, the adjacent edge gap does not comprise cathode catalysts, and the adjacent edge gap is suitable for liquid or gas flow; a cross-shaped adjacent angle gap is arranged between adjacent corners of each of the tiny units, at least one edge of the adjacent angle gap comprises cathode catalysts, and the tiny units are connected through the cathode catalysts in the adjacent angle gaps. The ordered integrated fuel cell membrane electrode of the present invention has high power density and good catalyst activity, and the overall performance of the fuel cell of the present invention is significantly improved, the production cost is low, and it is conducive to large-scale production and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of fuel cells, and in particular, relates to an ordered integrated fuel cell membrane electrode and a preparation method thereof. Background Art

[0002] In order to obtain higher power to support its application in heavy equipment, fuel cells often use large-area membrane electrodes to prepare fuel cells. Therefore, during the normal use of large-area membrane electrodes, local flooding is more likely to occur, affecting the diffusion of gas in the entire catalyst layer, resulting in a large area of ​​catalyst unable to contact the reaction gas, forming a local dead zone, and causing the battery performance to decline. In order to solve this problem, technicians usually replace conventional catalysts and carbon paper in membrane electrodes with new materials to change their porosity. For example, Korean patent KR 20170100293 A discloses that the performance of membrane electrodes is improved by using porous three-dimensional nanocatalysts, and Korean patent KR 20200123944 A discloses that the catalytic layer voids are regulated by introducing porous carbon carriers. However, the new materials introduced by these methods have high production costs and complex chemical preparation processes, which are not conducive to large-scale production and application.

[0003] Therefore, it is necessary to develop fuel cell membrane electrodes with new structures based on existing materials to solve the problem of water flooding of fuel cell membrane electrodes during operation and the problem of decreased membrane electrode power density caused by the inability to remove water from the catalyst layer in time and the inability of local catalysts to contact the reaction gas. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present invention is to propose an ordered integrated fuel cell membrane electrode and a preparation method and application thereof, which effectively alleviates the flooding problem during the use of large-area membrane electrodes, reduces oxygen transmission resistance, has high power density, and good catalyst activity. The overall performance of the fuel cell of the present invention is significantly improved, the production cost is low, and it is conducive to large-scale production and application.

[0005] In the first aspect of the present invention, the present invention proposes an ordered integrated fuel cell membrane electrode. According to an embodiment of the present invention, it includes: a cathode catalyst layer, the cathode catalyst layer includes a plurality of tiny units, the tiny units are distributed in an array, and the tiny units include cathode catalysts; wherein the shape of the tiny units is a polygon; a straight-line adjacent edge gap is set between the adjacent edges of each of the tiny units, the adjacent edge gap does not include cathode catalysts, and the adjacent edge gap is suitable for liquid or gas flow; a cross-shaped adjacent corner gap is set between the adjacent corners of each of the tiny units, at least one side of the adjacent corner gap includes cathode catalysts, and the tiny units are connected through the cathode catalysts in the adjacent corner gaps. The ordered integrated fuel cell membrane electrode according to the embodiment of the present invention effectively alleviates the flooding problem during the use of large-area membrane electrodes, reduces oxygen transmission resistance, has high power density, and good catalyst activity. The overall performance of the fuel cell made using the membrane electrode of the present invention is significantly improved, the production cost is low, and it is conducive to large-scale production and application.

[0006] According to an embodiment of the present invention, the lateral gap and / or the longitudinal gap of the adjacent angular gaps contain cathode catalysts, thereby ensuring smooth connection between the micro-units and uniform distribution of current in the catalyst layer without affecting water discharge.

[0007] According to an embodiment of the present invention, the cathode catalyst content in the adjacent corner gaps is lower than the cathode catalyst content in the micro-units relative to the total area of ​​the adjacent side gaps and the adjacent corner gaps, thereby further promoting the discharge of water or gas.

[0008] According to an embodiment of the present invention, the cathode catalyst content in the adjacent corner gaps is no more than 0.001% of the cathode catalyst content in the micro-units relative to the total area of ​​the adjacent side gaps and the adjacent corner gaps, based on the weight of the cathode catalyst contained in the unit area. Thus, on the one hand, the discharge efficiency of water and gas is improved, and the oxygen transmission resistance is reduced, and on the other hand, the micro-units are connected to ensure that the current can be evenly distributed.

[0009] According to an embodiment of the present invention, the cathode catalyst content in the adjacent angular gaps is 0.0001% to 0.001% of the cathode catalyst content in the micro-units.

[0010] According to an embodiment of the present invention, the aperture of the gap is 0.025 to 0.17 mm. The inventor has determined this preferred range through a large number of experiments. Within this aperture range, the ordered integrated fuel cell membrane electrode of the present invention has a high membrane electrode power density, good catalyst activity, and improved overall fuel cell performance.

[0011] According to an embodiment of the present invention, the aperture of the gap is 0.05-0.15 mm. Thus, the membrane electrode power density and catalytic activity are further improved, and the overall performance of the fuel cell is further improved.

[0012] According to an embodiment of the present invention, the aperture of the gap is 0.075-0.125 mm. Thus, the overall performance of the fuel cell can be further improved.

[0013] In some preferred embodiments, the diameter of the gap is 0.075 mm, 0.08 mm, 0.09 mm, 0.1 mm, 0.11 mm, 0.12 mm, or 0.125 mm.

[0014] According to an embodiment of the present invention, the shape of the micro-unit is a parallelogram or a rectangle, thereby further shortening the drainage path and accelerating the drainage speed of water from the inside of the catalyst layer.

[0015] According to an embodiment of the present invention, the area of ​​the micro-unit is 0.25-2.25 mm 2 The inventors have determined this preferred range through a large number of experiments. Within this area range, the ordered integrated fuel cell membrane electrode of the present invention has a higher membrane electrode power density, good catalyst activity, and improved overall fuel cell performance.

[0016] According to an embodiment of the present invention, the area of ​​the micro-unit is 0.25-1.25 mm 2 As a result, the membrane electrode power density and catalytic activity are further improved, and the overall performance of the fuel cell is further improved.

[0017] According to an embodiment of the present invention, the area of ​​the micro-unit is 0.9-1.1 mm 2 As a result, the membrane electrode power density and catalytic activity are further improved, and the overall performance of the fuel cell is further improved.

[0018] In some preferred embodiments, the area of ​​the micro-unit is 0.9 mm 2 , 0.95 mm 2 , 1.0 mm 2 , 1.05 mm 2 , 1.10 mm 2 .

[0019] According to an embodiment of the present invention, the fuel cell membrane electrode further includes: an anode catalyst layer; a proton exchange membrane, the cathode catalyst layer and the anode catalyst layer are respectively attached to the two sides of the proton exchange membrane; and a gas diffusion layer, a gas diffusion layer is respectively arranged on both sides of the proton exchange membrane.

[0020] According to an embodiment of the present invention, the area of ​​the gas diffusion layer overlaps with the area of ​​the cathode catalyst layer and the area of ​​the anode catalyst layer, thereby further improving the overall performance of the membrane electrode.

[0021] According to an embodiment of the present invention, the gas diffusion layer is a carbon paper with a microporous layer on one side, and the microporous layer of the carbon paper is arranged toward two sides of the proton exchange membrane.

[0022] According to an embodiment of the present invention, the proton exchange membrane is selected from one of a nafion perfluorosulfonate proton exchange acid membrane, a non-fluorinated polymer proton exchange membrane, and a composite membrane.

[0023] According to an embodiment of the present invention, the platinum loading of the anode catalyst layer is 0.1-0.3 mg / cm 2 The platinum loading of the cathode catalyst layer is 0.1-0.5 mg / cm 2 .

[0024] In a second aspect of the present invention, the present invention provides a method for preparing the aforementioned ordered integrated fuel cell membrane electrode.

[0025] Those skilled in the art will appreciate that the features and advantages described above for the fuel cell membrane electrode are also applicable to this method and will not be described in detail herein.

[0026] According to an embodiment of the present invention, it includes: preparing a cathode catalyst layer; the preparation of the cathode catalyst layer includes: subjecting the array mold and the transfer film to a first hot pressing treatment to obtain a first transfer film, the first transfer film contains an array mold, and the array mold is processed with an array distribution pattern corresponding to the micro-units; spraying cathode catalyst slurry on the side of the first transfer film containing the array mold to obtain a second transfer film, the second transfer film contains the cathode catalyst; separating or removing the array mold in the second transfer film to obtain a third transfer film, the cathode catalyst layer is formed on the third transfer film. According to the method of the embodiment of the present invention, it can be prepared using conventional catalysts, carbon paper and other materials used in the preparation of existing membrane electrodes, with low production cost, simple operation, and conducive to large-scale production and application.

[0027] According to an embodiment of the present invention, it also includes: preparation of an anode catalyst layer; the preparation of the anode catalyst layer includes: spraying an anode catalyst slurry on one side of a proton exchange membrane to obtain a first proton exchange membrane, on which the anode catalyst layer is formed; stacking the first proton exchange membrane on top of the third transfer membrane, with the side of the third transfer membrane on which the cathode catalyst layer is formed and the side of the first proton exchange membrane on which the anode catalyst layer is formed both placed upward, performing a second hot pressing treatment to obtain a second proton exchange membrane; separating or removing the transfer membrane in the second proton exchange membrane, so that the cathode catalyst layer is separated from the transfer membrane and attached to the proton exchange membrane, to obtain a third proton exchange membrane, with the cathode catalyst layer and the anode catalyst layer attached to both sides of the third proton exchange membrane.

[0028] According to an embodiment of the present invention, the method further includes: providing a gas diffusion layer on both sides of the third proton exchange membrane.

[0029] According to an embodiment of the present invention, the gas diffusion layer is a carbon paper with a microporous layer on one side, and the microporous layer of the carbon paper is arranged toward both sides of the third proton exchange membrane. After a third hot pressing treatment, the fuel cell membrane electrode is obtained.

[0030] According to an embodiment of the present invention, the array mold is a metal mesh mold.

[0031] According to an embodiment of the present invention, the diameter of the metal wire of the metal mesh mold is 0.025-0.17 mm.

[0032] According to an embodiment of the present invention, the diameter of the metal wire of the metal mesh mold is 0.05-0.15 mm.

[0033] According to an embodiment of the present invention, the diameter of the metal wire of the metal mesh mold is 0.075-0.125 mm.

[0034] According to an embodiment of the present invention, the unit hole area of ​​the metal mesh mold is 0.25-2.25 mm 2 .

[0035] According to an embodiment of the present invention, the unit hole area of ​​the metal mesh mold is 0.25-1.25 mm 2 .

[0036] According to an embodiment of the present invention, the unit hole area of ​​the metal mesh mold is 0.9-1.1 mm 2 .

[0037] According to an embodiment of the present invention, the material of the metal mesh mold is selected from at least one of tungsten, nickel and molybdenum.

[0038] According to an embodiment of the present invention, the cathode catalyst slurry or the anode catalyst slurry includes: a platinum-carbon catalyst, a nafion membrane solution, ethanol or isopropanol, and water.

[0039] According to an embodiment of the present invention, the mass percentage of platinum in the platinum-carbon catalyst is 40% to 60%, preferably 60%, relative to the mass of the platinum-carbon catalyst.

[0040] According to an embodiment of the present invention, relative to the mass of the nafion membrane solution, the mass percentage of nafion in the nafion membrane solution is 5% to 20%.

[0041] According to an embodiment of the present invention, the mass ratio of the platinum-carbon catalyst, the nafion membrane solution, ethanol or isopropanol, and water is 10:(15-30):125:125.

[0042] According to an embodiment of the present invention, the mass ratio of the platinum-carbon catalyst, the nafion membrane solution, ethanol or isopropanol, and water is 10:(17-28):125:125.

[0043] According to an embodiment of the present invention, the mass ratio of the platinum-carbon catalyst, the nafion membrane solution, ethanol or isopropanol, and water is 10:(18-27):125:125.

[0044] According to an embodiment of the present invention, the transfer film is a thermal transfer film.

[0045] In some specific embodiments of the present invention, the transfer film is selected from one of PET (polyethylene terephthalate) thermal transfer film, PVC (polyvinyl chloride film) thermal transfer film, and PTFE (polytetrafluoroethylene) thermal transfer film.

[0046] According to an embodiment of the present invention, the temperature of the hot pressing treatment is 130-150° C., the pressure is 2-8 MPa, and the time is 2-10 min.

[0047] In a third aspect of the present invention, a fuel cell, a fuel cell group or a fuel cell system is provided. According to an embodiment of the present invention, the fuel cell comprises: the ordered integrated fuel cell membrane electrode or the ordered integrated fuel cell membrane electrode prepared according to the method.

[0048] Those skilled in the art will appreciate that the features and advantages described above for the fuel cell membrane electrode and its preparation method are also applicable to the fuel cell, fuel cell stack or fuel cell system, and will not be described in detail here.

[0049] In a fourth aspect of the present invention, the present invention proposes the use of the aforementioned ordered integrated fuel cell membrane electrode or the aforementioned method in the preparation of a fuel cell, a fuel cell group or a fuel cell system.

[0050] Those skilled in the art will appreciate that the features and advantages described above for the fuel cell membrane electrode and its preparation method are also applicable to this application and will not be described in detail here.

[0051] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0053] Figure 1 A process flow chart of preparing an integrated membrane electrode according to one embodiment of the present invention;

[0054] Figure 2 This is an enlarged schematic diagram of the surface of the cathode catalyst layer of the integrated membrane electrode prepared in Example 1 of the present invention;

[0055] Figure 3 The photos of the micro-units in the cathode catalyst layer of the integrated membrane electrode prepared in Example 1 of the present invention under an optical microscope, wherein (A) is an optical microscope photo under a bright field, and the arrows point to a small number of connections between the micro-units and adjacent micro-units; (B) is an optical microscope photo under a dark field, and the arrows point to a small number of connections between the micro-units and adjacent micro-units, the black area is the area where the catalyst is located, and the white area is the light-transmitting area without catalyst;

[0056] Figure 4 A comparison diagram of polarization curves of the integrated membrane electrode prepared in Example 1 of the present invention and the conventional membrane electrode prepared in Comparative Example 1;

[0057] Figure 5 This is a comparison chart of the ohmic impedance of the integrated membrane electrode prepared in Example 1 of the present invention and the conventional membrane electrode prepared in Comparative Example 1.

[0058] Figure numerals: 1: hot press; 2: hot stage; 3: transfer film; 4: metal mesh mold; 5: pneumatic spray gun; 6: proton exchange membrane; 7: carbon paper. DETAILED DESCRIPTION

[0059] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0060] In the description of the present invention, it should be understood that the terms "thickness", "upper", "lower", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, "multiple" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0061] In the present invention, unless otherwise clearly specified and limited, the terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be fixed connection, detachable connection, or integrated; it can be mechanical connection or electrical connection; it can be directly connected or indirectly connected through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly specified. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances. In the present invention, unless otherwise clearly specified and limited, the first feature "above" or "below" the second feature can be that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, the first feature "above", "above" and "above" the second feature can mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. The first feature "below", "below" and "below" the second feature can be that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0062] The present invention proposes an ordered integrated fuel cell membrane electrode, a preparation method thereof, a fuel cell, a fuel cell group or a fuel cell system comprising the same, and applications thereof. The implementation principle and process thereof will be described in detail below.

[0063] Fuel cell membrane electrode

[0064] The present invention proposes an ordered integrated fuel cell membrane electrode. According to an embodiment of the present invention, it comprises: a cathode catalyst layer, the cathode catalyst layer comprises a plurality of tiny units, the tiny units are distributed in an array, and the tiny units comprise cathode catalysts; wherein the shape of the tiny units is a polygon; a straight-line adjacent edge gap is arranged between adjacent edges of each of the tiny units, the adjacent edge gap does not comprise cathode catalysts, and the adjacent edge gap is suitable for liquid or gas flow; a cross-shaped adjacent angle gap is arranged between adjacent corners of each of the tiny units, at least one edge of the adjacent angle gap comprises cathode catalysts, and the tiny units are connected through the cathode catalysts in the adjacent angle gaps. The ordered integrated fuel cell membrane electrode according to an embodiment of the present invention effectively alleviates the flooding problem during the use of large-area membrane electrodes, reduces oxygen transmission resistance, has high membrane electrode power density, and good catalyst activity. The overall performance of the fuel cell made using the membrane electrode of the present invention is significantly improved, the production cost is low, and it is conducive to large-scale production and application.

[0065] The water generated during the operation of the fuel cell can be quickly discharged through the gap structure of the ordered integrated fuel cell membrane electrode of the present invention, and the drainage path is short, so that the reaction gas can effectively reach various positions of the catalyst layer, thereby improving the performance of the membrane electrode.

[0066] According to the ordered integrated fuel cell membrane electrode of the embodiment of the present invention, the micro-units are distributed in an array, allowing the water vapor inside the catalyst layer to be more evenly distributed. The catalyst present in the gap between the adjacent corners of each micro-unit connects the electrochemical reactions between each micro-unit, which can effectively promote the uniform distribution of current.

[0067] In order to further accelerate the water discharge rate, in some specific embodiments of the present invention, the amount of cathode catalyst contained in the adjacent angular gap is reduced relative to the cathode catalyst contained in the micro-unit.

[0068] According to an embodiment of the present invention, at least one side of the adjacent angular gaps contains a cathode catalyst, thereby facilitating the uniform distribution of current without affecting water discharge.

[0069] In this document, the term "one side of a cross-shaped adjacent angular gap" refers to a half of the lateral gap or longitudinal gap of the cross-shaped adjacent angular gap, and the cross-shaped adjacent angular gap has four sides in total.

[0070] According to an embodiment of the present invention, the transverse gap and / or the longitudinal gap between the adjacent angular gaps contain cathode catalysts, thereby ensuring smooth connection between the micro units and ensuring uniform distribution of current in the catalyst layer.

[0071] According to an embodiment of the present invention, the cathode catalyst content in the adjacent corner gaps is lower than the cathode catalyst content in the micro-units relative to the total area of ​​the adjacent side gaps and the adjacent corner gaps, thereby further promoting the discharge of water or gas.

[0072] According to an embodiment of the present invention, the cathode catalyst content in the adjacent corner gaps is no more than 0.001% of the cathode catalyst content in the micro-units relative to the total area of ​​the adjacent side gaps and the adjacent corner gaps, based on the weight of the cathode catalyst contained in the unit area. Thus, on the one hand, the discharge efficiency of water and gas is improved, and the oxygen transmission resistance is reduced, and on the other hand, the micro-units are connected to ensure that the current can be evenly distributed.

[0073] According to an embodiment of the present invention, the cathode catalyst content in the adjacent angular gaps is 0.0001% to 0.001% of the cathode catalyst content in the micro-units.

[0074] In some specific embodiments, the cathode catalyst content in the adjacent angular gaps is 0.0001%, 0.00015%, 0.0002%, 0.00025%, 0.0003%, 0.00035%, 0.0004%, 0.00045%, 0.0005%, 0.00055%, 0.0006%, 0.00065%, 0.0007%, 0.00075%, 0.0008%, 0.00085%, 0.0009%, 0.00095%, or 0.001% of the cathode catalyst content of the microunit.

[0075] According to an embodiment of the present invention, the aperture of the gap is 0.025 to 0.17 mm. The inventor has determined this preferred range through a large number of experiments. Within this aperture range, the ordered integrated fuel cell membrane electrode of the present invention has a high membrane electrode power density, good catalyst activity, and improved overall fuel cell performance.

[0076] According to an embodiment of the present invention, the aperture of the gap is 0.05-0.15 mm. Thus, the membrane electrode power density and catalytic activity are further improved, and the overall performance of the fuel cell is further improved.

[0077] In some specific embodiments, the pore size of the gap is 0.05 mm, 0.075 mm, 0.1 mm, 0.125 mm, or 0.15 mm.

[0078] According to an embodiment of the present invention, the aperture of the gap is 0.075-0.125 mm. Thus, the overall performance of the fuel cell can be further improved.

[0079] In some preferred embodiments, the aperture of the gap is 0.075 mm, 0.08 mm, 0.09 mm, 0.1 mm, 0.11 mm, 0.12 mm, or 0.125 mm.

[0080] According to an embodiment of the present invention, the shape of the micro-unit is a parallelogram or a rectangle, thereby further shortening the drainage path and accelerating the drainage speed of water from the inside of the catalyst layer.

[0081] According to an embodiment of the present invention, the area of ​​the micro-unit is 0.25-2.25 mm 2 The inventors have determined this preferred range through a large number of experiments. Within this area range, the ordered integrated fuel cell membrane electrode of the present invention has a higher membrane electrode power density, good catalyst activity, and improved overall fuel cell performance.

[0082] According to an embodiment of the present invention, the area of ​​the micro-unit is 0.25-1.25 mm 2 As a result, the membrane electrode power density and catalytic activity are further improved, and the overall performance of the fuel cell is further improved.

[0083] According to an embodiment of the present invention, the area of ​​the micro-unit is 0.9-1.1 mm 2 As a result, the membrane electrode power density and catalytic activity are further improved, and the overall performance of the fuel cell is further improved.

[0084] In some specific embodiments, the area of ​​the micro-unit is 0.25 mm 2 , 0.3mm 2 , 0.35mm 2 , 0.4mm 2 , 0.45mm 2 , 0.5mm 2 , 0.55mm 2 , 0.60mm 2 , 0.65mm 2 , 0.7mm 2 , 0.75mm 2 , 0.8mm 2 , 0.85mm 2 , 0.9mm 2 , 0.95mm 2 , 1.0mm 2 , 1.05mm 2 , 1.10mm 2 , 1.15mm 2 , 1.2mm 2 , 1.25mm 2 .

[0085] In some preferred embodiments, the area of ​​the micro-unit is 0.9 mm 2 , 0.95mm 2 , 1.0mm 2 , 1.05mm 2 , 1.10mm 2 .

[0086] According to an embodiment of the present invention, the fuel cell membrane electrode further includes: an anode catalyst layer; a proton exchange membrane, the cathode catalyst layer and the anode catalyst layer are respectively attached to the two sides of the proton exchange membrane; and a gas diffusion layer, a gas diffusion layer is respectively arranged on both sides of the proton exchange membrane.

[0087] According to an embodiment of the present invention, the area of ​​the gas diffusion layer overlaps with the area of ​​the cathode catalyst layer and the area of ​​the anode catalyst layer, thereby further improving the overall performance of the membrane electrode.

[0088] In this article, the term “areal area overlap” refers to the precise alignment and integration of different functional layers in the multilayer structure of a fuel cell membrane electrode (MEA).

[0089] According to an embodiment of the present invention, the gas diffusion layer is a carbon paper with a microporous layer on one side, and the microporous layer of the carbon paper is arranged toward two sides of the proton exchange membrane.

[0090] According to an embodiment of the present invention, the proton exchange membrane is selected from one of a nafion perfluorosulfonate proton exchange acid membrane, a non-fluorinated polymer proton exchange membrane, and a composite membrane.

[0091] According to an embodiment of the present invention, the platinum loading of the anode catalyst layer is 0.1-0.3 mg / cm 2 The platinum loading of the cathode catalyst layer is 0.1-0.5 mg / cm 2 .

[0092] Preparation method

[0093] The present invention provides a method for preparing the above-mentioned ordered integrated fuel cell membrane electrode.

[0094] Those skilled in the art will appreciate that the features and advantages described above for the fuel cell membrane electrode are also applicable to this method and will not be described in detail here.

[0095] According to an embodiment of the present invention, it includes: preparing a cathode catalyst layer; the preparation of the cathode catalyst layer includes: subjecting the array mold and the transfer film to a first hot pressing treatment to obtain a first transfer film, the first transfer film contains an array mold, and the array mold is processed with an array distribution pattern corresponding to the micro-units; spraying cathode catalyst slurry on the side of the first transfer film containing the array mold to obtain a second transfer film, the second transfer film contains the cathode catalyst; separating or removing the array mold in the second transfer film to obtain a third transfer film, the cathode catalyst layer is formed on the third transfer film. According to the method of the embodiment of the present invention, it can be prepared using conventional catalysts, carbon paper and other materials used in the preparation of existing membrane electrodes, with low production cost, simple operation, and conducive to large-scale production and application.

[0096] According to an embodiment of the present invention, it also includes: preparation of an anode catalyst layer; the preparation of the anode catalyst layer includes: spraying an anode catalyst slurry on one side of a proton exchange membrane to obtain a first proton exchange membrane, on which the anode catalyst layer is formed; stacking the first proton exchange membrane on top of the third transfer membrane, with the side of the third transfer membrane on which the cathode catalyst layer is formed and the side of the first proton exchange membrane on which the anode catalyst layer is formed both placed upward, performing a second hot pressing treatment to obtain a second proton exchange membrane; separating or removing the transfer membrane in the second proton exchange membrane, so that the cathode catalyst layer is separated from the transfer membrane and attached to the proton exchange membrane, to obtain a third proton exchange membrane, with the cathode catalyst layer and the anode catalyst layer attached to both sides of the third proton exchange membrane.

[0097] According to an embodiment of the present invention, the method further includes: providing a gas diffusion layer on both sides of the third proton exchange membrane.

[0098] According to an embodiment of the present invention, the gas diffusion layer is a carbon paper with a microporous layer on one side, the microporous layer of the carbon paper is arranged toward both sides of the third proton exchange membrane, and a third hot pressing treatment is performed to obtain the fuel cell membrane electrode.

[0099] As known to those skilled in the art, the array mold should be able to withstand the above-mentioned hot pressing treatment; and after the cathode catalyst slurry spraying treatment on the transfer membrane is completed, the array mold can be easily separated or removed from the transfer membrane containing the cathode catalyst.

[0100] Exemplarily, the material of the array mold may be metal or high molecular plastic material such as polyimide.

[0101] According to an embodiment of the present invention, the array mold is a metal mesh mold.

[0102] According to an embodiment of the present invention, the diameter of the metal wire of the metal mesh mold is 0.025-0.17 mm.

[0103] According to an embodiment of the present invention, the diameter of the metal wire of the metal mesh mold is 0.05-0.15 mm.

[0104] According to an embodiment of the present invention, the diameter of the metal wire of the metal mesh mold is 0.075-0.125 mm.

[0105] According to an embodiment of the present invention, the unit hole area of ​​the metal mesh mold is 0.25-2.25 mm 2 .

[0106] According to an embodiment of the present invention, the unit hole area of ​​the metal mesh mold is 0.25-1.25 mm 2 .

[0107] According to an embodiment of the present invention, the unit hole area of ​​the metal mesh mold is 0.9-1.1 mm 2 .

[0108] According to an embodiment of the present invention, the material of the metal mesh mold is selected from at least one of tungsten, nickel and molybdenum. In some specific embodiments, metal wires are woven into a mesh mold, and since the diameter of the metal wires is uniform and the area of ​​the fabric unit holes is controllable, an array mold can be obtained quickly and conveniently.

[0109] According to an embodiment of the present invention, the cathode catalyst slurry or the anode catalyst slurry includes: a platinum-carbon catalyst; a nafion membrane solution; ethanol or isopropanol; and water.

[0110] According to an embodiment of the present invention, the mass percentage of platinum in the platinum-carbon catalyst is 40% to 60%, preferably 60%, relative to the mass of the platinum-carbon catalyst.

[0111] According to an embodiment of the present invention, relative to the mass of the nafion membrane solution, the mass percentage of nafion in the nafion membrane solution is 5% to 20%, preferably 20%.

[0112] In this article, the term "nafion membrane" refers to a perfluorosulfonic acid polymer (perfluorosulfonic acid ion exchange membrane) developed by DuPont, which is a composite material composed of many identical polymer molecules. It is commercially available.

[0113] According to an embodiment of the present invention, the mass ratio of the platinum-carbon catalyst, the nafion membrane solution, ethanol or isopropanol, and water is 10:(15-30):125:125.

[0114] According to an embodiment of the present invention, the mass ratio of the platinum-carbon catalyst, the nafion membrane solution, ethanol or isopropanol, and water is 10:(17-28):125:125.

[0115] According to an embodiment of the present invention, the mass ratio of the platinum-carbon catalyst, the nafion membrane solution, ethanol or isopropanol, and water is 10:(18-27):125:125.

[0116] In some specific embodiments of the present invention, the cathode catalyst slurry or the anode catalyst slurry is obtained by the following method: 200 mg of a platinum-carbon catalyst with a mass percentage of 60% platinum, 360 mg of a 20% nafion membrane solution, 2.5 g of isopropanol, and 2.5 g of water are taken and ultrasonically treated.

[0117] In some specific embodiments of the present invention, the cathode catalyst slurry or the anode catalyst slurry is obtained by the following method: 200 mg of a platinum-carbon catalyst with a mass percentage of 60% platinum, 340 mg of a 20% nafion membrane solution, 2.5 g of ethanol, and 2.5 g of water are taken and ultrasonically treated.

[0118] In some specific embodiments of the present invention, the cathode catalyst slurry or the anode catalyst slurry is obtained by the following method: take 200 mg of a platinum-carbon catalyst with a mass percentage of 50% platinum, 450 mg of a nafion membrane solution with a mass percentage of 20%, 2.5 g of isopropanol, and 2.5 g of water, and perform ultrasonic treatment.

[0119] In some specific embodiments of the present invention, the cathode catalyst slurry or the anode catalyst slurry is obtained by the following method: 200 mg of a platinum-carbon catalyst with a mass percentage of 40% platinum, 540 mg of a 20% nafion membrane solution, 2.5 g of ethanol, and 2.5 g of water are taken and ultrasonically treated.

[0120] In some specific embodiments of the present invention, the cathode catalyst slurry or the anode catalyst slurry is obtained by the following method: 200 mg of a platinum-carbon catalyst with a mass percentage of 60% platinum, 340 mg of a nafion membrane solution with a mass percentage of 20%, 2.5 g of isopropanol, and 2.5 g of water are taken and ultrasonically treated.

[0121] According to an embodiment of the present invention, the ultrasonic treatment time is not less than 20 min, preferably 20 min.

[0122] According to an embodiment of the present invention, the transfer film is a thermal transfer film.

[0123] In some specific embodiments of the present invention, the transfer film is selected from one of PET (polyethylene terephthalate) thermal transfer film, PVC (polyvinyl chloride film) thermal transfer film, and PTFE (polytetrafluoroethylene) thermal transfer film.

[0124] In some specific embodiments of the present invention, the thickness of the transfer film is greater than or equal to 250 μm.

[0125] In some specific embodiments of the present invention, the transfer film has a thickness of 250 to 350 μm.

[0126] In some specific embodiments of the present invention, the temperature of the hot pressing treatment is 130-150° C., the pressure is 2-8 MPa, and the time is 2-10 min.

[0127] According to an embodiment of the present invention, the temperature of the first hot pressing treatment is 130-150° C., the pressure is 5-8 MPa, and the time is 4-6 min, preferably 130° C., 5 MPa, and 5 min.

[0128] According to an embodiment of the present invention, the temperature of the second hot pressing treatment is 130-150° C., the pressure is 2-4 MPa, and the time is 6-10 min, preferably 130° C., 2 MPa, and 8 min.

[0129] According to an embodiment of the present invention, the temperature of the third hot pressing treatment is 130-150° C., the pressure is 2-4 MPa, and the time is 2-6 min, preferably 130° C., 2 MPa, and 2 min.

[0130] Fuel cell, fuel cell stack or fuel cell system

[0131] The present invention provides a fuel cell, a fuel cell group or a fuel cell system. According to an embodiment of the present invention, it includes: the ordered integrated fuel cell membrane electrode as described above or the ordered integrated fuel cell membrane electrode prepared according to the method as described above.

[0132] Those skilled in the art will appreciate that the features and advantages described above for the fuel cell membrane electrode and its preparation method are also applicable to the fuel cell, fuel cell stack or fuel cell system, and will not be described in detail here.

[0133] application

[0134] The present invention proposes the use of the aforementioned ordered integrated fuel cell membrane electrode or the aforementioned method in the preparation of a fuel cell, a fuel cell group or a fuel cell system.

[0135] Those skilled in the art will appreciate that the features and advantages described above for the fuel cell membrane electrode and its preparation method are also applicable to this application and will not be described in detail here.

[0136] Unless otherwise specified, the carbon paper in the examples or comparative examples of the present invention is a carbon paper with a microporous layer on one side.

[0137] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0138] Example 1

[0139] Take 200 mg of commercial platinum-carbon catalyst with a platinum content of 60%, 360 mg of 20% nafion membrane solution by mass, 2.5 g of isopropanol, and 2.5 g of water, add them into a 10 ml vial, mix well, and ultrasonicate for 20 minutes to prepare the slurry required for spraying membrane electrode.

[0140] like Figure 1 As shown in A, a 300 μm thick PTFE (polytetrafluoroethylene) thermal transfer film (20 cm × 20 cm) (i.e., transfer film 3) is placed flat on a hot stage 2, and a tungsten metal mesh mold 4 (with a unit pore area of ​​1 mm 2 , tungsten wire diameter 0.1mm) is placed on the transfer film 3. The transfer film 3 and the metal mesh mold 4 are hot pressed by a hot press 1 until the two are fully combined, the hot pressing temperature is 130°C, the pressure is 5Mpa, and the time is 5min.

[0141] like Figure 1 As shown in B in the figure, the hot-pressed transfer film 3 and the metal mesh mold 4 are placed on the adsorption hot stage with the metal mesh facing upward, and the slurry required for spraying the membrane electrode is added to the pneumatic spray gun 5 of the spraying equipment. When the temperature of the adsorption hot stage rises to 80°C, the pneumatic spray gun 5 is used to spray the slurry on the surface of the transfer film 3 to form a square cathode catalyst layer with a side length of 5 cm.

[0142] The proton exchange membrane 6 is placed on an adsorption hot stage, and the slurry is sprayed on one side of the proton exchange membrane 6 in the same spraying manner to form a square anode catalyst layer with a side length of 5 cm, thereby obtaining an anode catalyst layer attached to the proton exchange membrane 6 .

[0143] After all the spraying is completed, the transfer film 3 and the metal mesh mold 4 are separated with tweezers to obtain the transfer film 3 with an ordered integrated cathode catalyst layer. During the separation operation, care should be taken not to slide the metal mesh mold to avoid damage to the ordered catalyst layer on the transfer film.

[0144] like Figure 1As shown in C, the transfer membrane 3 is placed on the hot table 2 of the hot press 1 with the side with the ordered integrated cathode catalyst layer facing upward. The proton exchange membrane 6 is placed on top of the transfer membrane 3 with the side with the anode catalyst layer facing upward, wherein the catalyst layers on the transfer membrane 3 and the proton exchange membrane 6 must be kept overlapping to avoid mismatching of the cathode and cathode catalyst layers after hot pressing. Start the hot press 1 to hot press the proton exchange membrane 6 and the transfer membrane 3 (hot pressing temperature is 130°C, pressure is 2Mpa, and time is 8min). After the hot pressing is completed, wait for the temperature of the transfer membrane 3 to cool to room temperature, peel off the transfer membrane 3, and the cathode catalyst layer falls off from the transfer membrane 3 and adheres to the surface of the proton exchange membrane 6, thereby obtaining a proton exchange membrane 6 with an ordered integrated cathode catalyst layer.

[0145] Finally, if Figure 1 As shown in D in the figure, two pieces of carbon paper 7 are placed on both sides of the proton exchange membrane 6 with the microporous layer facing inward, wherein the carbon paper 7 should overlap with the catalytic layer on both sides of the proton exchange membrane 6. The clamped proton exchange membrane 6 and carbon paper 7 are placed on the hot stage 2 of the hot press 1 and hot pressed (hot pressing temperature is 130°C, pressure is 2Mpa, time is 2min), and finally a highly ordered integrated membrane electrode (effective area is 25cm 2 ).

[0146] The enlarged schematic diagram of the cathode catalyst layer surface of the integrated membrane electrode prepared in this embodiment is as follows: Figure 2 As shown in the figure, the micro-units in the cathode catalyst layer are photographed under an optical microscope. Figure 3 shown.

[0147] The results show:

[0148] (1) The cathode catalyst layer of the integrated membrane electrode is composed of a parallelogram-shaped micro-unit array. In the entire cathode catalyst layer, the parallelogram-shaped micro-units are distributed in an orderly manner ( Figure 2 ). (2) The area of ​​these parallelogram micro-units is 1 mm 2 , and the surface of the catalyst layer is smooth without obvious cracks ( Figure 3 There is a gap of 0.1 mm between the micro-units, and there is a small amount of connection between each micro-unit and the adjacent micro-units ( Figure 3 B); based on the weight of the cathode catalyst contained per unit area, the cathode catalyst content in the gap is 0.00015% of the cathode catalyst content in the micro unit.

[0149] The above results show that the method of Example 1 can obtain a 2The ordered integrated cathode catalyst layer is composed of a parallelogram array of tiny units. In the array composed of these tiny units, there is a gap of 0.1 mm between each tiny unit, and there is a small amount of connection between each tiny unit and the adjacent tiny units. Moreover, the surface of the ordered integrated cathode catalyst layer is flat and has no obvious cracks. Using the ordered integrated cathode catalyst layer, a highly ordered integrated membrane electrode can be further obtained.

[0150] Example 2

[0151] The difference between this embodiment and embodiment 1 is that the unit hole area of ​​the metal mesh mold 4 is 1.25 mm 2 , the diameter of the tungsten wire is 0.1mm.

[0152] The magnified observation results of the micro-units in the cathode catalyst layer of the integrated membrane electrode prepared in this embodiment under an optical microscope show that: (1) the cathode catalyst layer of the integrated membrane electrode is composed of a parallelogram micro-unit array, and the parallelogram micro-units are distributed in an orderly manner throughout the cathode catalyst layer. (2) The area of ​​these parallelogram micro-units is 1.25 mm 2 , and the surface of the catalyst layer is flat without obvious cracks. (3) There is a gap of 0.1 mm between the micro-units, and there is a small amount of connection between each micro-unit and the adjacent micro-units; based on the weight of the cathode catalyst contained per unit area, the cathode catalyst content in the gap is 0.00012% of the cathode catalyst content in the micro-unit.

[0153] Example 3

[0154] The difference between this embodiment and embodiment 1 is that the unit hole area of ​​the metal mesh mold 4 is 0.25mm 2 , the diameter of the tungsten wire is 0.1mm.

[0155] The magnified observation results of the micro-units in the cathode catalyst layer of the integrated membrane electrode prepared in this embodiment under an optical microscope show that: (1) the cathode catalyst layer of the integrated membrane electrode is composed of a parallelogram micro-unit array, and the parallelogram micro-units are distributed in an orderly manner throughout the cathode catalyst layer. (2) The area of ​​these parallelogram micro-units is 0.25 mm 2 , and the surface of the catalyst layer is flat without obvious cracks. (3) There is a gap of 0.1 mm between the micro-units, and there is a small amount of connection between each micro-unit and the adjacent micro-units; based on the weight of the cathode catalyst contained per unit area, the cathode catalyst content in the gap is 0.0006% of the cathode catalyst content in the micro-unit.

[0156] Example 4

[0157] The difference between this embodiment and embodiment 1 is that the unit hole area of ​​the metal mesh mold 4 is 1.25 mm 2 , the diameter of the tungsten wire is 0.05mm.

[0158] The magnified observation results of the micro-units in the cathode catalyst layer of the integrated membrane electrode prepared in this embodiment under an optical microscope show that: (1) the cathode catalyst layer of the integrated membrane electrode is composed of a parallelogram micro-unit array, and the parallelogram micro-units are distributed in an orderly manner throughout the cathode catalyst layer. (2) The area of ​​these parallelogram micro-units is 1.25 mm 2 , and the surface of the catalyst layer is flat without obvious cracks. (3) There is a gap of 0.05 mm between the micro-units, and there is a small amount of connection between each micro-unit and the adjacent micro-units; based on the weight of the cathode catalyst contained per unit area, the cathode catalyst content in the gap is 0.0001% of the cathode catalyst content in the micro-unit.

[0159] Example 5

[0160] The difference between this embodiment and embodiment 1 is that the unit hole area of ​​the metal mesh mold 4 is 0.25mm 2 , the diameter of the tungsten wire is 0.05mm.

[0161] The magnified observation results of the micro-units in the cathode catalyst layer of the integrated membrane electrode prepared in this embodiment under an optical microscope show that: (1) the cathode catalyst layer of the integrated membrane electrode is composed of a parallelogram micro-unit array, and the parallelogram micro-units are distributed in an orderly manner throughout the cathode catalyst layer. (2) The area of ​​these parallelogram micro-units is 0.25 mm 2 , and the surface of the catalyst layer is flat without obvious cracks. (3) There is a gap of 0.05 mm between the micro-units, and there is a small amount of connection between each micro-unit and the adjacent micro-units; based on the weight of the cathode catalyst contained per unit area, the cathode catalyst content in the gap is 0.0005% of the cathode catalyst content in the micro-unit.

[0162] Example 6

[0163] The difference between this embodiment and embodiment 1 is that the unit hole area of ​​the metal mesh mold 4 is 1.0 mm 2 , the diameter of the tungsten wire is 0.05mm.

[0164] The magnified observation results of the micro-units in the cathode catalyst layer of the integrated membrane electrode prepared in this embodiment under an optical microscope show that: (1) the cathode catalyst layer of the integrated membrane electrode is composed of a parallelogram micro-unit array, and the parallelogram micro-units are distributed in an orderly manner throughout the cathode catalyst layer. (2) The area of ​​these parallelogram micro-units is 1.0 mm 2 , and the surface of the catalyst layer is flat without obvious cracks. (3) There is a gap of 0.05 mm between the micro-units, and there is a small amount of connection between each micro-unit and the adjacent micro-units; based on the weight of the cathode catalyst contained per unit area, the cathode catalyst content in the gap is 0.000125% of the cathode catalyst content in the micro-unit.

[0165] Example 7

[0166] The difference between this embodiment and embodiment 1 is that the unit hole area of ​​the metal mesh mold 4 is 1.25 mm 2 , the diameter of the tungsten wire is 0.15mm.

[0167] The magnified observation results of the micro-units in the cathode catalyst layer of the integrated membrane electrode prepared in this embodiment under an optical microscope show that: (1) the cathode catalyst layer of the integrated membrane electrode is composed of a parallelogram micro-unit array, and the parallelogram micro-units are distributed in an orderly manner throughout the cathode catalyst layer. (2) The area of ​​these parallelogram micro-units is 1.25 mm 2 , and the surface of the catalyst layer is flat without obvious cracks. (3) There is a gap of 0.15 mm between the micro-units, and there is a small amount of connection between each micro-unit and the adjacent micro-units; based on the weight of the cathode catalyst contained per unit area, the cathode catalyst content in the gap is 0.0002% of the cathode catalyst content in the micro-unit.

[0168] Example 8

[0169] The difference between this embodiment and embodiment 1 is that the unit hole area of ​​the metal mesh mold 4 is 0.25mm 2 , the diameter of the tungsten wire is 0.15mm.

[0170] The magnified observation results of the micro-units in the cathode catalyst layer of the integrated membrane electrode prepared in this embodiment under an optical microscope show that: (1) the cathode catalyst layer of the integrated membrane electrode is composed of a parallelogram micro-unit array, and the parallelogram micro-units are distributed in an orderly manner throughout the cathode catalyst layer. (2) The area of ​​these parallelogram micro-units is 0.25 mm 2, and the surface of the catalyst layer is flat without obvious cracks. (3) There is a gap of 0.15 mm between the micro-units, and there is a small amount of connection between each micro-unit and the adjacent micro-units; based on the weight of the cathode catalyst contained per unit area, the cathode catalyst content in the gap is 0.001% of the cathode catalyst content in the micro-unit.

[0171] Example 9

[0172] The difference between this embodiment and embodiment 1 is that the unit hole area of ​​the metal mesh mold 4 is 1.0 mm 2 , the diameter of the tungsten wire is 0.15mm.

[0173] The magnified observation results of the micro-units in the cathode catalyst layer of the integrated membrane electrode prepared in this embodiment under an optical microscope show that: (1) the cathode catalyst layer of the integrated membrane electrode is composed of a parallelogram micro-unit array, and the parallelogram micro-units are distributed in an orderly manner throughout the cathode catalyst layer. (2) The area of ​​these parallelogram micro-units is 1.0 mm 2 , and the surface of the catalyst layer is flat without obvious cracks. (3) There is a gap of 0.15 mm between the micro-units, and there is a small amount of connection between each micro-unit and the adjacent micro-units; based on the weight of the cathode catalyst contained per unit area, the cathode catalyst content in the gap is 0.00025% of the cathode catalyst content in the micro-unit.

[0174] Example 10

[0175] Compared with Example 1, this example is different in that 200 mg of a commercial platinum-carbon catalyst with a platinum content of 50%, 450 mg of a 20% nafion membrane solution by mass, 2.5 g of isopropanol, and 2.5 g of water are added to a 10 ml vial, mixed evenly, and ultrasonicated for 20 minutes to prepare the slurry required for the spray membrane electrode.

[0176] The magnified observation of the micro-units in the cathode catalyst layer of the integrated membrane electrode prepared in this embodiment under an optical microscope is consistent with that in Embodiment 1.

[0177] Embodiment 11

[0178] Compared with Example 1, this example is different in that: 200 mg of a commercial platinum-carbon catalyst with a platinum content of 40%, 540 mg of a 20% nafion membrane solution by mass, 2.5 g of isopropanol, and 2.5 g of water are added to a 10 ml vial, mixed evenly, and ultrasonicated for 20 minutes to prepare the slurry required for the spray membrane electrode.

[0179] The magnified observation of the micro-units in the cathode catalyst layer of the integrated membrane electrode prepared in this embodiment under an optical microscope is consistent with that in Embodiment 1.

[0180] Example 12

[0181] Compared with Example 1, this example is different in that: 200 mg of a commercial platinum-carbon catalyst with a platinum content of 60%, 360 mg of a 20% nafion membrane solution by mass, 2.5 g of ethanol, and 2.5 g of water are added to a 10 ml vial, mixed evenly, and ultrasonicated for 20 minutes to prepare the slurry required for the spray membrane electrode.

[0182] The magnified observation of the micro-units in the cathode catalyst layer of the integrated membrane electrode prepared in this embodiment under an optical microscope is consistent with that in Embodiment 1.

[0183] Comparative Example 1

[0184] Compared with Example 1, the difference between this comparative example and Example 1 is that the cathode catalyst layer is prepared by a conventional transfer method. Specifically, a PTFE (polytetrafluoroethylene) transfer film 3 (20 cm×20 cm) with a thickness of 300 microns is placed flat on an adsorption hot plate, and the slurry required for spraying the membrane electrode is added to the pneumatic spray gun 5 of the spraying equipment. When the temperature of the adsorption hot plate rises to 80°C, the pneumatic spray gun 5 is used to spray the slurry required for spraying the membrane electrode on the surface of the transfer film 3 to form a square cathode catalyst layer with a side length of 5 cm.

[0185] Comparative Example 2

[0186] Compared with Example 11, the difference between this comparative example and Example 11 is that the cathode catalyst layer is prepared by a conventional transfer method. Specifically, a PTFE (polytetrafluoroethylene) transfer film 3 (20 cm×20 cm) with a thickness of 300 microns is placed flat on an adsorption hot plate, and the slurry required for spraying the membrane electrode is added to the pneumatic spray gun 5 of the spraying equipment. When the temperature of the adsorption hot plate rises to 80°C, the pneumatic spray gun 5 is used to spray the slurry required for spraying the membrane electrode on the surface of the transfer film 3 to form a square cathode catalyst layer with a side length of 5 cm.

[0187] Comparative Example 3

[0188] Compared with Example 12, the difference between this comparative example and Example 12 is that the cathode catalyst layer is prepared by a conventional transfer method. Specifically, a PTFE (polytetrafluoroethylene) transfer film 3 (20 cm×20 cm) with a thickness of 300 microns is placed flat on an adsorption hot plate, and the slurry required for spraying the membrane electrode is added to the pneumatic spray gun 5 of the spraying equipment. When the temperature of the adsorption hot plate rises to 80°C, the pneumatic spray gun 5 is used to spray the slurry required for spraying the membrane electrode on the surface of the transfer film 3 to form a square cathode catalyst layer with a side length of 5 cm.

[0189] Performance investigation of integrated membrane electrodes prepared in Examples 1 to 12 and Comparative Examples 1 to 3

[0190] Table 1: Performance test results of integrated membrane electrode prepared in Examples 1 to 12 and Comparative Examples 1 to 3

[0191]

[0192]

[0193] The above results show that: compared with comparative examples 1 to 3, (1) the rated power @ 0.67V (mW) of the integrated membrane electrodes of Examples 1 to 12 is significantly improved as a whole, generally up to 750 to 900mW, indicating that the power density is effectively improved. (2) The peak power of the integrated membrane electrodes of Examples 1 to 12 is also improved, indicating that the catalyst activity is improved. (3) The high-frequency resistance HFR of the integrated membrane electrodes of Examples 1 to 12 is significantly reduced as a whole, generally reduced by about 30mΩ, indicating that due to the existence of the gap, the water in the catalyst layer can be better transferred to the gas diffusion layer and the proton exchange membrane, so that there is sufficient water in the membrane and the proton conductivity performance is improved.

[0194] Furthermore, the inventors compared the polarization curves and ohmic impedance of the integrated membrane electrode prepared in Example 1 and the conventional membrane electrode prepared in Comparative Example 1. The results showed that ( Figure 4 , Figure 5 ): The rated power density of the integrated membrane electrode of Example 1 is increased by nearly 30%, because the gas can diffuse from the gap position to each micro-membrane electrode, so that more catalysts can contact the reaction raw materials, greatly improving the battery performance at the rated voltage. In addition, the peak power density of the micro-membrane electrode is significantly improved. This is because under high current, the ordered integrated membrane electrode can make the gas reach the catalyst surface faster, reducing the oxygen transmission resistance. And the water management is improved, so that the ohmic impedance of the membrane is significantly reduced.

[0195] Therefore, the fuel cell made by using the integrated membrane electrode of the present invention solves the technical problem that water cannot be discharged from the inside of the catalyst layer in time, further improves water management, and improves the performance of the fuel cell. Specifically, the power density of the fuel cell is effectively improved, which is beneficial for reducing the volume and weight of the fuel cell; the catalyst activity of the fuel cell is further improved; the proton conduction performance of the fuel cell membrane is further improved, the ohmic loss is low, and the battery durability is good.

[0196] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0197] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing an ordered integrated fuel cell membrane electrode, characterized in that: The ordered integrated fuel cell membrane electrode comprises: a cathode catalyst layer, the cathode catalyst layer comprises a plurality of micro-units, the micro-units are arranged in an array, and the micro-units comprise cathode catalysts; wherein the micro-units are in the shape of polygons; a straight-line adjacent edge gap is arranged between adjacent edges of each of the micro-units, the adjacent edge gap does not comprise cathode catalysts, and the adjacent edge gap is suitable for liquid or gas flow; a cross-shaped adjacent angle gap is arranged between adjacent corners of each of the micro-units, at least one side of the adjacent angle gap comprises cathode catalysts, and the micro-units are connected through the cathode catalysts in the adjacent angle gaps; wherein the aperture of the gap is 0.05 to 0.15 mm; The method comprises: preparing a cathode catalyst layer and preparing an anode catalyst layer; Wherein, the preparation of the cathode catalyst layer comprises: Performing a first heat pressing process on the array mold and the transfer film to obtain a first transfer film, wherein the first transfer film contains the array mold, and the array mold is processed with an array distribution pattern corresponding to the micro-units; Spraying cathode catalyst slurry on the side of the first transfer film containing the array mold to obtain a second transfer film, wherein the second transfer film contains the cathode catalyst; Separating or removing the array mold in the second transfer film to obtain a third transfer film, on which the cathode catalyst layer is formed; The preparation of the anode catalyst layer comprises: spraying an anode catalyst slurry on one side of a proton exchange membrane to obtain a first proton exchange membrane, wherein the anode catalyst layer is formed on the first proton exchange membrane; The first proton exchange membrane is stacked on the third transfer membrane, with the side of the third transfer membrane on which the cathode catalyst layer is formed and the side of the first proton exchange membrane on which the anode catalyst layer is formed both placed upward, and a second hot pressing treatment is performed to obtain a second proton exchange membrane; Separating or removing the transfer membrane in the second proton exchange membrane, separating the cathode catalyst layer from the transfer membrane and attaching it to the proton exchange membrane, to obtain a third proton exchange membrane, wherein the cathode catalyst layer and the anode catalyst layer are attached to both sides of the third proton exchange membrane; It also includes: a gas diffusion layer is respectively arranged on both sides of the third proton exchange membrane; the gas diffusion layer is a carbon paper with a microporous layer on one side, the microporous layer of the carbon paper is arranged toward both sides of the third proton exchange membrane, and a third hot pressing treatment is performed to obtain the fuel cell membrane electrode.

2. The method for preparing an ordered integrated fuel cell membrane electrode according to claim 1, characterized in that: Measured by the weight of the cathode catalyst contained per unit area, relative to the total area of ​​the adjacent side gaps and the adjacent corner gaps, the cathode catalyst content in the adjacent corner gaps does not exceed 0.001% of the cathode catalyst content in the micro-unit.

3. The method for preparing an ordered integrated fuel cell membrane electrode according to claim 1, characterized in that: The aperture of the gap is 0.075-0.125 mm.

4. The method for preparing an ordered integrated fuel cell membrane electrode according to claim 1, characterized in that: The shape of the micro-unit is a parallelogram or a rectangle, and the area of ​​the micro-unit is 0.25 to 1.25 mm 2 .

5. The method for preparing an ordered integrated fuel cell membrane electrode according to claim 1, characterized in that: The fuel cell membrane electrode further comprises: Anode catalyst layer; A proton exchange membrane, wherein the cathode catalyst layer and the anode catalyst layer are respectively attached to two sides of the proton exchange membrane; A gas diffusion layer, wherein a gas diffusion layer is disposed on both sides of the proton exchange membrane; The area of ​​the gas diffusion layer overlaps with the area of ​​the cathode catalyst layer and the area of ​​the anode catalyst layer.

6. The method for preparing an ordered integrated fuel cell membrane electrode according to claim 5, characterized in that: The gas diffusion layer is a carbon paper with a microporous layer on one side, and the microporous layer of the carbon paper is arranged toward both sides of the proton exchange membrane; The proton exchange membrane is selected from one of a nafion perfluorosulfonate proton exchange acid membrane, a non-fluorinated polymer proton exchange membrane, and a composite membrane.

7. The method for preparing an ordered integrated fuel cell membrane electrode according to claim 5, characterized in that: The platinum loading of the anode catalyst layer is 0.1 to 0.3 mg / cm 2 The platinum loading of the cathode catalyst layer is 0.1-0.5 mg / cm 2 .

8. The method for preparing an ordered integrated fuel cell membrane electrode according to claim 1, characterized in that: The array mold is a metal mesh mold; The diameter of the metal wire of the metal mesh mold is 0.025 to 0.17 mm; The unit hole area of ​​the metal mesh mold is 0.25 to 1.25 mm 2 ; The material of the metal mesh mold is selected from at least one of tungsten, nickel and molybdenum; The transfer film is a thermal transfer film, selected from one of a PET thermal transfer film, a PVC thermal transfer film, and a PTFE thermal transfer film.

9. The method for preparing an ordered integrated fuel cell membrane electrode according to claim 1, characterized in that: The temperature of the hot pressing treatment is 130-150° C., the pressure is 2-8 MPa, and the time is 2-10 min.

10. The method for preparing an ordered integrated fuel cell membrane electrode according to claim 1, characterized in that: The cathode catalyst slurry comprises: a platinum-carbon catalyst, a nafion membrane solution, ethanol or isopropanol, and water; the mass percentage of platinum in the platinum-carbon catalyst is 40% to 60%, and the mass percentage of nafion in the nafion membrane solution is 5% to 20%; The mass ratio of the platinum-carbon catalyst, the nafion membrane solution, ethanol or isopropanol, and water is 10:(15-30):125:

125.

11. The method for preparing an ordered integrated fuel cell membrane electrode according to claim 1, characterized in that: The anode catalyst slurry comprises: a platinum-carbon catalyst, a nafion membrane solution, ethanol or isopropanol, and water; the mass percentage of platinum in the platinum-carbon catalyst is 40% to 60%, and the mass percentage of nafion in the nafion membrane solution is 5% to 20%; The mass ratio of the platinum-carbon catalyst, the nafion membrane solution, ethanol or isopropanol, and water is 10:(15-30):125:

125.

12. A fuel cell, a fuel cell stack or a fuel cell system, characterized in that: include: An ordered integrated fuel cell membrane electrode prepared by the method according to any one of claims 1 to 11.